Teoria das trocas sociais: um estudo em crianças com transtorno de déficit de atenção/hiperatividade (TDAH) - Bastos, Caroline Benezath Rodrigues (2015)
This research investigated, in a psychogenetic perspective, the aspects of social exchange from 14 female children diagnosed with Attention Deficit Hyperactivity Disorder (ADHD), seven children aged between 7 and 8 years and seven aged between 10 and 11 years, which are treated at Pediatric Clinic of University Hospital Cassiano Antônio Moraes. Data were collected through two instruments. The first consisted in reading two boards, containing each one a cutout of a comic story for children that presents situations of social exchanges between the characters, followed by an interview based on Piaget’s Clinical Method. The second instrument was the Piagetian Proof of Conservation of Substance, which aimed to find out if the child has the ability to logical reversibility, which, according to Piaget, is required for social exchanges balanced. The procedures were recorded on audio and video and the information collected was later inserted into protocols. Data were analyzed qualitatively, from pre-prepared categories based on Piaget’s concepts. The results revealed that, regardless of age, most of the established social exchanges were balanced. However, it was observed prevalence of exchanges that indicate spontaneous and non-normative reciprocity, typical of the previous developmental stage (preoperational) at that the participants should be (concrete operational). Regarding the unbalanced social exchanges, it was observed that, in almost all, there was an increased of debt feelings displayed by the participants to the people with whom they interact socially. It was also observed contradiction between what the participants think that other should do and what they themselves would do, so that when they speak directly about themselves, there is, generally, a change of opinion towards what is socially accepted. Moreover, the great majority of participants in both age groups do not have yet the notion of logical reversibility. However, inasmuch as the children grow old, it was observed an evolution towards the acquiring this notion. In short, the results revealed that most of participants showed balanced social exchanges without having the ability to logical reversibility, and allow hypothesize that individuals with the ability to logical reversibility are necessarily able to express social balanced exchanges, but not necessarily manifest them in all situations.